Application of Financial Statement Preparation based on SAK EMKM in Pempek Lestari23 MSMEs - Octavia, Ika Nur; Sari, Dhany Efita (Proceedings International Conference on Education Innovation and Social Science, 2024)
Financial statements are part of the management and operational transparency of a company, including Micro, Small, and Medium Enterprises (MSMEs). This article examines the preparation of financial statements based on the SAK EMKM in Pempek Lestari23. The purpose of this study is to describe the application of financial report preparation based on SAK EMKM and describe the obstacles in the preparation of financial statements for Pempek Lestari23 MSMEs. This study uses a qualitative method with a case study approach to one the MSMEs operating in the city of Surakarta. Data was collected through in-depth interviews with MSME owners, as well as analysis of financial statement documents that had been pepared. The results of the study show that although the implementation of SAK EMKM provides a clear and structured framework for MSMEs in compiling financial statements, there are several obstacles such as limited accounting understanding, limited resources, and the need for further training. However, the implementation of SAK EMKM also brings significant benefits, including improved finances, ease of access to financing, and strengthening support and training for MSME actors as well as simplify accounting procedures so that SAK EMKM can be implemented more effectively and efficiently.